Avaliação da linguagem oral e escrita no pré-escolar e nos primeiros anos de escolaridade - Batalha, Joana; Lobo, Maria; Estrela, Antónia; Bragança, Bruna (Revista da Associação Portuguesa de Linguística, 2021)
In this article, we present an assessment instrument aimed at diagnosing oral language and reading and writing skills in children attending pre-school (5 years) and the early years of primary school. The instrument was mainly designed for the school context, and it was developed in collaboration with kindergarten educators and primary teachers who participated in PIPALE - Preventive Intervention Project for Reading and Writing, a project which is integrated in the National Program for the Promotion of School Success. The instrument covers the assessment of phonological and syntactic awareness, comprehension of syntactic structures, early literacy, and reading and writing skills (word reading, word and sentence writing, text comprehension, and text production). Besides offering a detailed description of the structure and tasks of the instrument, the present study includes the results of the first implementation of this tool to a total of 495 students in pre-school, first grade and second grade. The results show significant differences between the three groups (pre-school, first grade and second grade) in phonological awareness (identification of initial syllable, initial phoneme and final rhyme) and between the younger groups and the second graders in syntactic awareness (acceptability judgement task) and early literacy skills. As for reading and writing skills, the results show better performance in reading tasks than in writing tasks, a strong significant correlation between phonological awareness and word reading and word writing, and between literacy skills and word reading and writing. We also found a milder correlation between syntactic awareness and reading comprehension, as well as text writing. These results suggest that the instrument is effective for an early diagnosis and early intervention of reading and writing skills.